2022
DOI: 10.3390/children9111642
|View full text |Cite
|
Sign up to set email alerts
|

Early-Onset Neonatal Sepsis in Turkey: A Single-Center 7-Year Experience in Etiology and Antibiotic Susceptibility

Abstract: Background: The pathogen distribution and antibiotic susceptibility of the pathogens in early-onset sepsis (EOS) differ between countries. The epidemiological data from a limited number of studies about EOS in Turkey are insufficient. In this study, we aimed to evaluate the culture-proven EOS cases, causative microorganisms, antibiotic susceptibility patterns, and risk factors for mortality in EOS. Methods: This is a retrospective, single-center study over a 7-year period, from 2013 to 2020, at Zeynep Kamil Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…In a study conducted in Türkiye, cases of early-onset neonatal sepsis were investigated and 27.6% (8 out of 29) of E. coli strains were found to be ESBL positive; all of these ESBL producers were susceptible to gentamicin. 20 A study investigating the epidemiology of culture-proven neonatal sepsis from Saudi Arabia reported that all isolated gram-negative and grampositive bacteria were susceptible to aminoglycoside antibiotics (amikacin and/or gentamicin) tested. 21 This retrospective, laboratory data-based study had some limitations.…”
Section: Discussionmentioning
confidence: 99%
“…In a study conducted in Türkiye, cases of early-onset neonatal sepsis were investigated and 27.6% (8 out of 29) of E. coli strains were found to be ESBL positive; all of these ESBL producers were susceptible to gentamicin. 20 A study investigating the epidemiology of culture-proven neonatal sepsis from Saudi Arabia reported that all isolated gram-negative and grampositive bacteria were susceptible to aminoglycoside antibiotics (amikacin and/or gentamicin) tested. 21 This retrospective, laboratory data-based study had some limitations.…”
Section: Discussionmentioning
confidence: 99%
“…Engorgement is swelling and distension of the breasts, usually in the early days of initiation of lactation, caused by vascular dilation as well as the arrival of the early milk, and the women may experience extreme fullness, tightness, and pain in the breasts. Additionally, the skin may appear shiny and stretched, and the breasts may feel warm to the touch 19 .…”
Section: Methodsmentioning
confidence: 99%